2011
DOI: 10.1007/s10641-011-9895-y
|View full text |Cite
|
Sign up to set email alerts
|

Subtle ‘boom and bust’ response of Macquaria ambigua to flooding in an Australian dryland river

Abstract: The ecology of dryland rivers is driven by their highly variable hydrology, particularly flooding regimes, whereby intermittent floods typically generate 'booms' of primary and secondary productivity, including massive fish production. We tested these concepts in the Moonie River, Australia, using the percichthyid, Macquaria ambigua, a dryland river species known to display pronounced 'boom and bust' abundance patterns in response to floodplain inundation followed by extended periods of low to no channel flow.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 31 publications
2
17
0
Order By: Relevance
“…The data analysed in this study derive from 13 sampling occasions in the Moonie River from 10 waterholes selected as per the Cooper Creek waterholes and covered both in‐channel and overland flow events (Sternberg et al ., ). The first sampling occasion (T1, Feb 2006) occurred some 6 weeks after a high channel flow event, and the most recent overland flood event (14 000 ML day −1 ) occurred some 3 years prior to T1 (Sternberg et al ., ). Throughout the study period (T1–T13), there were three overland flood events (17 000 ML day −1 in Feb 2008, 13 500 ML day −1 in May 2009 and 81 000 ML day −1 in March 2010 just prior to T13).…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…The data analysed in this study derive from 13 sampling occasions in the Moonie River from 10 waterholes selected as per the Cooper Creek waterholes and covered both in‐channel and overland flow events (Sternberg et al ., ). The first sampling occasion (T1, Feb 2006) occurred some 6 weeks after a high channel flow event, and the most recent overland flood event (14 000 ML day −1 ) occurred some 3 years prior to T1 (Sternberg et al ., ). Throughout the study period (T1–T13), there were three overland flood events (17 000 ML day −1 in Feb 2008, 13 500 ML day −1 in May 2009 and 81 000 ML day −1 in March 2010 just prior to T13).…”
Section: Methodsmentioning
confidence: 97%
“…Thus, similar to Cooper Creek, the Moonie River exists for most of the year as a series of disconnected waterholes although the duration of zero flow is longer in Cooper Creek (Balcombe and Sternberg, ). The data analysed in this study derive from 13 sampling occasions in the Moonie River from 10 waterholes selected as per the Cooper Creek waterholes and covered both in‐channel and overland flow events (Sternberg et al ., ). The first sampling occasion (T1, Feb 2006) occurred some 6 weeks after a high channel flow event, and the most recent overland flood event (14 000 ML day −1 ) occurred some 3 years prior to T1 (Sternberg et al ., ).…”
Section: Methodsmentioning
confidence: 98%
“…, 2008). In the Moonie catchment, ongoing research has revealed only limited evidence for the boom and bust productivity model (Sternberg et al. , 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Like M. ambigua , M. australiense is likely to be a proficient disperser with evidence for strong migratory behaviour (Lee & Fielder, 1979). Furthermore, high abundances of M. australiense after flow provide some evidence for high recruitment and migration during connectivity events (Sternberg et al. , 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, fish densities during these surveys were well below the estimated carrying capacity, and survival was relatively stable across age classes. In addition, the interpretation made by Sternberg et al (2011) arguably pertains more to the absence of a boom in postflood recruitment, when resource availability is high, than to the likely effects of resource limitation. There are also no published examples in which crowding (i.e., density-dependent) effects have been linked to the mortality of this species, suggesting the response to crowding may also be subtle.…”
Section: Demographic Parametersmentioning
confidence: 99%